Correlation between Knowledge and Attitudes with COVID-19 Prevention Behavior in High School Students in Surabaya Raya, East Java, Indonesia - Laura Navika Yamani; Erni Astutik; Novia Indah Puspitasari; Yasmin Nihayatun Nadzifah; Siti Qamariyah Khairunisa (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The SARS-CoV-2 virus that causes COVID-19 continues to mutate, with some forming new, relatively more dangerous variants. Surabaya Raya including Surabaya, Sidoarjo, and Gresik is the most affected areas by the COVID-19 pandemic, especially in East Java Province. One of the reasons for the increase in COVID-19 cases is due to inappropriate COVID-19 prevention behavior. Knowledge and attitudes are important factors that can influence a person's behavior. This study aims to analyze the relationship between knowledge and attitudes toward COVID-19 prevention behavior in high school students. This type of research used analytic observational with a cross-sectional design. The subjects in this study were 176 students from SMA 4 Muhammadiyah Surabaya, SMA Negeri 1 Sidoarjo, and MA Mamba'ul Hisan Gresik who had filled in the questionnaire. The dependent variable in this study is COVID-19 prevention behavior. The independent variables in this study included gender, history of being infected with COVID-19, knowledge, and attitudes. Data were analyzed using the chi-square test. The variables studied that are related to COVID-19 prevention behavior in high school students are knowledge (p = 0.027; PR = 0.48) and attitudes (p = 0.000; PR = 6.83). The variables studied that did not have a relationship were gender (p = 0.537) and a history of being infected with COVID-19 (p = 0.974). Knowledge and attitudes are significantly related to COVID-19 prevention behavior, but not to gender and history of COVID-19 disease. Community service is one of the important efforts in improving the knowledge, attitudes, and behavior of high school students. Keywords: COVID-19, Knowledge, Attitude, Behavior.